Transfering Technology induced scenarios of digitized work - Bansmann, Michael; Fechtelpeter, Christian; Anacker, Harald; Dumitrescu, Roman (XXIX ISPIM Innovation Conference 2018, 17. - 20. Jun. 2018)

Planning of scalable Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen (Proceedings of the 2018 ISPIM Innovation Conference , Jun. 2018 International Society for Professional Innovation Management (ISPIM))

Building blocks for planning and implementation of smart services based on existing products - Mittag, Tobias; Rabe, Martin; Gradert, Till; Kühn, Arno; Dumitrescu, Roman (CIRP IPS², Linköping, 29. - 31. Mai 2018)

Analytics Canvas – A Framework for the Design and Specification of Data Analytics Projects - Kühn, Arno; Joppen, Robert; Reinhart, Felix; Röltgen, Daniel; von Enzberg, Sebastian; Dumitrescu, Roman (28th CIRP Design Conference 2018, Nantes, 23. - 25. Mai 2018)

Maturity Model-Based Planning of Cyber-Physical Systems in the Machinery and Plant Engineering Industry - Westermann, Thorsten; Dumitrescu, Roman (DESIGN Conference 2018, 21. - 24. Mai 2018)

Planning of Smart Services based on a Reference Architecture - Rabe, Martin; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (International Design Conference 2018, Dubrovnik, Kroatien , 21. - 24. Mai 2018)

Smart Services - Konzept einer neuen Marktleistung - Frank, Maximilian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Zukunftsorientierte Leistungssteigerung von Unternehmen durch Industrie 4.0 - Pierenkemper, Christoph; Drewel, Marvin; Gausemeier, Jürgen (Tagungsband AALE 2018 - Das Forum für Fachleute der Automatisierungstechnik aus Hochschulen und Wirtschaft, 15. Konferenz für Angewandte Automatisierungstechnik in Lehre und Entwicklung (AALE))

Morphological business model analysis to derive the dominant industry logic - Niewöhner, Nadine; Albers, Alexander; Rabe, Martin; Dumitrescu, Roman (Proceedings of the ISPIM Innovation Forum, Mrz. 2018 International Society for Professional Innovation Management (ISPIM))

A practical Framework for the Optimization of Production Management Processes - Joppen, Robert; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (The 16th Global Conference on Sustainable Manufacturing)

Supporting the planning phase of SME-tailored technology transfer projects - Fechtelpeter, Christian; Dumitrescu, Roman; Kühn, Arno (IAMOT 2018 - 27th International Association for Management of Technology Conference)

Entwicklung intelligenter technischer Systeme - Dumitrescu, Roman; Kühn, Arno; Thielemann, Frank; Steffen, Daniel (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Leistungssteigerung durch Industrie 4.0 für kleine und mittlere Unternehmen - Knospe, Olaf; Drewel, Marvin; Mittag, Tobias; Pierenkemper, Christoph; Hobscheidt, Daniela (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Toward A Design Approach For Industrial Indoor Location-Based Services (I²LBS) - Falkowski, Tommy; Günther, Matthias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman (DESIGN Conference 2018,)

Framework for the agile development of innovative Product-Service-Systems for existing physical rehabilitation systems - Asmar, Laban; Rabe, Martin; Low, Cheng Yee; Yee, Jingye; Kühn, Arno; Dumitrescu, Roman (4th International Conference on System-Integrated Intelligence: Intelligent, Flexible and Connected Systems in Products and Production)

Specification technique for augmented reality based product service systems - Röltgen, Daniel; Wortmann, Fabio; Dumitrescu, Roman (INTERNATIONAL DESIGN CONFERENCE - DESIGN 2018)

Eingesetzte wissenschaftliche Methoden - Kummert, Franz; Albers, Alexander; Bremer, Christian; Büttner, Sebastian; Dellnitz, Michael; Dumitrescu, Roman; Gräler, Manuel; Just, Viktor; Mucha, Henrik; Peitz, Sebastian; Röcker, Carsten; Trächtler, Ansgar; et al. (Ressourceneffiziente Selbstoptimierende Wäscherei – Ergebnisse des ReSerW-Projekts)

Systematic Development of Smart Factory using CONSENS - Mohammad, Ubaidullah; Low, Cheng Yee; Asmar, Laban; Rahman, Ramhuzaini Abd; Rabe, Martin; Dumitrescu, Roman; Zakaria, Noor Ayuni Che (4th International Conference on System-Integrated Intelligence: Intelligent, Flexible and Connected Systems in Products and Production)

PGE-Produktgenerationsentwicklung und Zukunftsvorausschau: Eine systematische Betrachtung zur Ermittlung der Zusammenhänge - Albers, Albert; Dumitrescu, Roman; Marthaler, Florian; Albers, Alexander; Kühfuss, Dennis; Strauch, Markus; Siebe, Andreas; Bursac, Nikola (14. Symposium für Vorausschau und Technologieplanung)

Electrodeposition of poly(acrylic acid) on stainless steel with enhanced adhesion properties - Meinderink, D.; Orive, A. G.; Grundmeier, Guido (Surface and Interface Analysis)

A combinatorial approach to enhance barrier properties of thin films on polymers: Seeding and capping of PECVD thin films by PEALD - Gebhard, Maximilian; Mitschker, Felix; Hoppe, Christian; Aghaee, Morteza; Rogalla, Detlef; Creatore, Mariadriana; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Plasma Processes and Polymers)

A combinatorial approach to enhance barrier properties of thin films on polymers: Seeding and capping of PECVD thin films by PEALD - Gebhard, Maximilian; Mitschker, Felix; Hoppe, Christian; Aghaee, Morteza; Rogalla, Detlef; Creatore, Mariadriana; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Plasma Processes and Polymers)

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg K. N.; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)

Influence of heat-pretreatments on the microstructural and mechanical properties of galfan-coated metal bonds - Hordych, Illia; Rodman, Dmytro; Nürnberger, Florian; Schmidt, Hans Christian; Orive, Alejandro Gonzalez; Homberg, Werner; Grundmeier, Guido; Maier, Hans Jürgen

Cold pressure welding of aluminium-steel blanks: Manufacturing process and electrochemical surface preparation - Schmidt, Hans Christian; Homberg, Werner; Orive, Alejandro Gonzalez; Grundmeier, Guido; Hordych, Illia; Maier, Hans Jürgen

Intelligente Steuerungen und Regelungen - Lüke, Christopher; Timmermann, Julia; Kessler, Jan Henning; Trächtler, Ansgar (Steigerung der Intelligenz mechatronischer Systeme)

Ressourceneffiziente Selbstoptimierende Wäscherei - Trächtler, Ansgar

Shader-Based Realtime Simulation of High-Definition Automotive Headlamps - Rüddenklau, Nico; Biemelt, Patrick; Henning, Sven; Gausemeier, Sandra; Trächtler, Ansgar (SIMUL 2018, The Tenth International Conference on Advances in System Simulation)

Rotordynamic instabilities in washing machines - Drüke, Simon; Bicker, Rainer; Schullter, Bernd; Henke, Christian; Trächtler, Ansgar (Proceedings of the 10th International Conference on Rotor Dynamics - IFToMM. Vol. 2. International Conference on Rotor Dynamics - IFToMM)

Assisted setup of forming processes: compensation of initial stochastic disturbances - Gräler, Manuel; Springer, Robert; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Swedish Production Symposium)

Umsetzung einer echtzeitfähigen Mehrgrößenoptimierung auf einer Industriesteuerung - Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (EKA 2018 Entwurf komplexer Automatisierungssysteme - Beschreibungsmittel, Methoden, Werkzeuge und Anwendungen)

Model based Setup Assistant for Progressive Tools - Springer, Robert; Graeler, Manuel; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (AIP Conference Proceedings)

Recent Developments in Hardware-in-the-Loop Testing - Millitzer, Jonathan; Mayer, Dirk; Jersch, Torben; Henke, Christian; Michael, Jan; Tamm, Christoph; Ranisch, Christopher (IMAC-XXXVI Conference and Exposition on Structural Dynamics)

A Simulation Framework for Testing a Conceptual Hierarchical Autonomous Traffic Management System including an Intelligent External Traffic Simulation - Henning, Sven; Biemelt, Patrick; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the DSC 2018 Europe VR: New trends in Human in the Loop simulation and testing. Driving simulation and VR)

A System-Level Design Framework for Networked Driving Simulation - Abdelgawad, Kareem

Holistic Requirements for Interdisciplinary Development Processes - Lankeit, Christopher; Michael, Jan; Henke, Christian; Trächtler, Ansgar (Proceedings 1st International Workshop on Learning from other Disciplines for Requirements Engineering)

Model-based precision position and force control of SMA actuators with a clamping application - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (Mechatronics)

Observer-based nonlinear control strategies for Hardware-in-the-Loop simulations of multiaxial suspension test rigs - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (Mechatronics)

Rapid-Control-Prototyping as part of Model-Based Development of Heat Pump Dryers - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Bockholt, Marcos; Möhlenkamp, Andreas; Katter, Michael (Procedia Manufacturing)

Modellbasierter Entwurf intelligenter mechatronischer Systeme mithilfe semantischer Technologien - Oestersötebier, Felix

A Model Predictive Motion Cueing Strategy for a 5-Degree-of-Freedom Driving Simulator with Hybrid Kinematics - Biemelt, Patrick; Henning, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR (DSC))

Eignungsbewertung eines Enterprise Architecture Frameworks für das IT-Alignment zwischen Unternehmensstrategie und IT-Landschaft am Beispiel der Arvato SCM - Funke, Lars Christian

How to Deal with Inaccurate Service Descriptions in On-The-Fly Computing: Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 23rd International Conference on Natural Language and Information Systems)
The vision of On-The-Fly Computing is an automatic composition of existing software services. Based on natural language software descriptions, end users will receive compositions tailored to their needs. For this reason, the quality of the initial software service description strongly determines whether a software composition really meets the expectations of end users. In this paper, we expose open NLP challenges needed to be faced for service composition in On-The-Fly Computing.
Keywords: Requirements Extraction; Temporal Reordering of Software Functions; Inaccuracy Compensation

Improving Classifiers for Semantic Annotation of Software Requirements with Elaborate Syntactic Structure - Kim, Yeongsu; Lee, Seungwoo; Dollmann, Markus; Geierhos, Michaela (International Journal of Advanced Science and Technology)
A user generally writes software requirements in ambiguous and incomplete form by using natural language; therefore, a software developer may have difficulty in clearly understanding what the meanings are. To solve this problem with automation, we propose a classifier for semantic annotation with manually pre-defined semantic categories. To improve our classifier, we carefully designed syntactic features extracted by constituency and dependency parsers. Even with a small dataset and a large number of classes, our proposed classifier records an accuracy of 0.75, which outperforms the previous model, REaCT.
Keywords: Software Engineering; Natural Language Processing; Semantic Annotation; Machine Learning; Feature Engineering; Syntactic Structure

Digitalisierungspotenziale in Geschäftsprozessen effizient und effektiv erkennen (Effective and Efficient Identification of Digitalization Potentials in Business Processes) - Rittmeier, Florian; Engels, Gregor; Teetz, Alexander (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)
Ein wichtiges Element der Digitalen Transformation ist die Digitalisierung der Prozesse in Unternehmen. Eine Herausforderung besteht hierbei in der systematischen Erkennung von Digitalisierungspotenzialen in Prozessen. Bestehende Ansätze benötigen Experten, welche Potenziale über ihre Erfahrung oder zeitaufwendig mithilfe von Musterkatalogen identifizieren. In diesem Artikel werden verschiedene Digitalisierungspotenziale klassifiziert und Muster für ein zukünftiges musterbasiertes Analyseverfahren zur automatisierten Identifikation von Digitalisierungspotenzialen in BPMN-Diagrammen beschrieben. Im Vergleich zu bestehenden Ansätzen erlaubt es Experten die Identifizierung von Digitalisierungspotenzialen effizienter und effektiver durchzuführen.
Keywords: Digitalisierungspotenziale; BPI; Digitale Transformation; Information Flow-Modellierung; Patterns; Requirements Engineering

Technology Integration into Existing Companies - Büsching, J.; Lindemann, C.; Jahnke, U.; Kruse, A.; Koch, R. (29th Annual International Solid Freeform Fabrication Symposium)
Theimplementation of additive manufacturing as an industrial manufacturing process poses extraordinary challenges to companies due to their far-reaching differences to conventional processes. In addition to the major differences in the production process, the pre and post process steps in particular also require a rethinking for companies and their employees. To overcome these challenges and specifically to assist SMEs in the integration of technologies five industrial companies are researching together within research project "OptiAMix", funded by the German Federal Ministry of Education and Research (BMBF) and coordinated by the Paderborn University. This paper focuses on the development of an optimal and standardized process chain and its implementation in a general integration methodology. This enables the standardized integration of additivemanufacturing in order to create a uniform understanding of the procedures and tasks within the company for the industrial application of additive manufacturing at an early stage as well as the full exploitation of its high potentials. Therefore, the methodology also includes other technology-specific components such as strategic component selection, decision support for "make or buy" and the implementation of automated component marking.

Monitoring für die Bahnhofsmissionen: Ein datengestütztes Instrument zur Organisationsentwicklung. Projektbeschreibung und Ergebnisdarstellung - Goller, Michael
Keywords: Bahnhofsmission; Survey Feedback; Monitoring

Rezension von Ahrenholz, Hövelbrinks & Schmellentin (Hrsg; 2017): Fachunterricht und Sprache in schulischen Lehr-/Lernprozessen. Tübingen: Narr Franke Attempto. - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Englischnoten und globale englische Sprachkompetenz in bilingualen Zweigen - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)

Empirische Zugänge zum bilingualen Sachfachunterricht - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)